IMUNOPATOGENESIS LEPTOSPIROSIS - Anggraini, Debie; Reni Lenggogeni (Nusantara Hasana Journal, 2024)
Leptospirosis is a zoonotic disease caused by bacteria from the genus *Leptospira*. This disease is one of the infectious diseases that are widespread throughout the world, especially in tropical and subtropical areas. Leptospirosis is transmitted to humans through direct contact with water, soil, or materials contaminated by the urine of infected animals. Animals such as rats, dogs, and livestock are often the main reservoirs of this bacteria. Humans can be infected when their skin or mucosa comes into contact with water or soil containing *Leptospira* bacteria, especially during floods or when working in wet environments. Clinically, leptospirosis can vary from asymptomatic infection to severe disease that can be fatal. Severe clinical manifestations, known as Weil's disease, can involve organ failure, including liver and kidney, and severe bleeding. In the context of the hematological and immunological systems, leptospirosis can cause disorders of blood cell function, including hemolytic anemia, thrombocytopenia, and changes in the leukocyte profile. The immune response to *Leptospira* is critical in determining disease severity, with uncontrolled immune mechanisms contributing to tissue and organ damage.